Urban America and its police : from the postcolonial era through the turbulent 1960s - Hahn, Harlan, 1939- (University Press of Colorado, 2003)
In Urban America and Its Police, Harlan Hahn and Judson L. Jeffries present a broad and comparative overview of urban policing in the United States. Synthesizing their own research with information from an eclectic array of sources-seminal social science studies of urban police departments, government documents, reports from organizations such as the American Civil Liberties Union, and think tank monographs-they present a nationally oriented and historically informed understanding of the diverse and often conflicting roles police officers play on city streets. Hahn and Jeffries also demonstrate the ways in which race and ethnicity have influenced United States law enforcement since the creation of the nation's first police force. Ultimately, the authors call for a renewed emphasis on the social service dimension of police work-a shift they argue would reduce crime and enhance community support for those who are sworn to project and serve.